1982
DOI: 10.1524/zkri.1982.159.14.255
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of iron(II) diphosphate, Fe2P2O7

Abstract: The preparation of Fe 2 P20 7 is described, with a technique to produce single crystals. The triclinic (PI) unit cell has the dimensions a = 5.517(2), b = 5.255(2), c = 4.488(l)Ä, α = 98.73(2)°, 0 = 98.33(4)°, γ = 103.81(2)°, V= 122.6(2)Ä 3 (Ζ = 1). The formula weight is 285.64atomic units, and the calculated density is 3.868 g · cm -3 . The crystal structure has been determined by direct methods and refined to R F = 0.049 on the basis of 722 independent X-ray single-crystal reflections (PW1100 diffractometer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…There are several structure-types in which the A 2 B 2 O 7 compounds crystallize. The structure of ␥-Cu 2 V 2 O 7 is most closely related to the structure of triclinic ␤-Fe 2 P 2 O 7 (Stefanidis & Nord 1982, Hoggins et al 1983. The unit-cell dimensions of ␤-Fe 2 P 2 O 7 (a 5.517, b 5.255, c 4.488 Å, ␣ 98.73, ␤ 98.33, ␥ 103.81°) are related to those of ␥-Cu 2 V 2 O 7 ( Table 1), except that the c parameter of ␥-Cu 2 V 2 O 7 is doubled owing to the higher degree of distortion of the V 2 O 7 groups in comparison to the P 2 O 7 groups.…”
Section: Relationships To the A 2 B 2 X 7 Compoundsmentioning
confidence: 96%
“…There are several structure-types in which the A 2 B 2 O 7 compounds crystallize. The structure of ␥-Cu 2 V 2 O 7 is most closely related to the structure of triclinic ␤-Fe 2 P 2 O 7 (Stefanidis & Nord 1982, Hoggins et al 1983. The unit-cell dimensions of ␤-Fe 2 P 2 O 7 (a 5.517, b 5.255, c 4.488 Å, ␣ 98.73, ␤ 98.33, ␥ 103.81°) are related to those of ␥-Cu 2 V 2 O 7 ( Table 1), except that the c parameter of ␥-Cu 2 V 2 O 7 is doubled owing to the higher degree of distortion of the V 2 O 7 groups in comparison to the P 2 O 7 groups.…”
Section: Relationships To the A 2 B 2 X 7 Compoundsmentioning
confidence: 96%
“…The crystal structure of Fe2P207 was determined by Stefanidis & Nord (1982) in space group P1, with Z=I.…”
Section: (Q) Diiron(ii) Diphosphate Fe2p207mentioning
confidence: 99%
“…More likely is that Stefandis & Nord have omitted the weak reflections Marsh (1981) has shown that such deletion of weak reflections biases the statistical tests towards acentric distributions. Hoggins et al (1983) in their paper took note of the work of Stefanidis & Nord (1982) and argued for a centrosymmetric structure on the basis of their statistical tests, and because of the high correlations between related parameters and the nonpositivedefinite temperature factors encountered when they refined the structure in the noncentrosymmetric space group.…”
Section: (Q) Diiron(ii) Diphosphate Fe2p207mentioning
confidence: 99%
See 1 more Smart Citation
“…Impurities of ferric iron or Fe 2 P 2 0 7 may give Mössbauer signals influencing the low-and highvelocity absorption profiles. However, the Mössbauer spectra for conceivable impurities are well known, and so are the X-ray diffraction data of Fe 2 P 2 0 7 (Stefanidis and Nord, 1982). Thus the maximum total amounts of impurities can be estimated to about 2 weight %.…”
Section: Figmentioning
confidence: 99%